Augmented Reality Reconstruction of Deteriorated Art - Romanos, César; León González, Daniel; Salas García, Marta; Galindo López, M. Cruz (Street Art & Urban Creativity, 2025)
ARRDA (Augmented Reality Reconstruction of Deteriorated Art) is a mobile app that leverages AR to revitalize the rural cultural heritage. The pilot, deployed for the Romanesque San Miguel church in Soria/Spain, allows the user to visualize the digital reconstructions of centuries-old, faded graffiti. Developed with Unity and ARFoundation, it enhances the visitor experience and gathers data related to the behavior and number of users. ARRDA seeks to preserve the cultural heritage and revitalize areas affected by the “España Vaciada” demographic challenge, fostering a cultural and emotional connection with forgotten cultural environments and our past.